Tinjauan Frasa “Setiap Orang” dalam Pasal 3 Ayat (1) Peraturan Pemerintah Nomor 56 Tahun 2021 tentang Pengelolaan Royalti Hak Cipta Lagu dan/atau Musik - Ilham, Fajar Hidayansyah; Ticoalu, Luna Dezeana (UI Scholars Hub, 2026)
Copyright is one form of legal protection for intellectual works, occupying an important position within the intellectual property law system. The Copyright Law explicitly grants exclusive rights to creators, encompassing both moral rights and economic rights. Economic rights, as stipulated in Article 9 paragraph (1), allow creators to obtain economic benefits from their works, ranging from publication, reproduction, distribution, performance, to communication to the public. This provision shows that creators hold a primary position as legal subjects entitled to protection, while also serving as central actors in the creative industry ecosystem. In practice, the mechanism for copyright protection requires implementing instruments that regulate the utilization of works, particularly in the context of commercial use. However, Article 3 paragraph (1) of Government Regulation No. 56 of 2021 introduces new issues. Article 3 paragraph (1) of PP 56/2021 can be interpreted as restricting those rights by imposing an obligation to pay royalties. In addition to creating a potential normative conflict, the practice of royalty collection by the National Collective Management Agency (LMKN) also raises questions regarding its effectiveness and fairness. This paper specifically examines the phrase “Every Person” in the context of Article 3 paragraph (1) of PP 56/2021 and its impact on the rights of creators, providing a critical review of the norm that has the potential to generate legal uncertainty.